Homegarden to Rebuild Environmental, Economic, Food and Nutritional Security in North & Eastern Provinces of Sri Lanka - Pushpakumara, D.K.N.G.; Jeyavanan, K.; Marambe, B.; Sivananthawerl, T.; Singh, V.P. (Tropical homegardens: multi functionality and benefits, World congress on Agroforestry (wca2014-2485) held at WijayanBhavan, Delhi, India, 2014)
Homegarden agroforestry is an integrated land management system that provides sustainable economic, environmental and social benefits to people through growing of appropriate but high value and cultural trees and crops and animals together in well planned and systematically managed cycles as a specialized way of farming. Experience from the other parts of Sri Lanka and elsewhere in the South Asian region revealed that during the last two decades, the scientific advances made in the field of homegarden agroforestry have laid the foundations for streamlining homegardens in the fight against poverty, hunger and land degradation. But until recently the up scaling or improvement of homegarden agroforestry systems remains poor throughout the northern and eastern provinces due to prevailed war. As in other areas of the country, homegarden agroforestry has received little attention from policy makers and research institutes. However, recently the Government of Sri Lanka launched a national homegarden improvement program (Divi Neguma) to make food and nutritional secure Sri Lanka. Selection of socio-culturally, nutritionally and environmentally important trees, crops and animal combinations; production of planting material of the selected trees and crops and multiplication of herds of animal species; measures to empower people to understand the past agroforestry land management principles and their interrelation with food and nutritional security and sustainable food production are identified as accelerators of the adoption of the national program. Networking of NARS institutes in the two provinces, train key scientists in the NARS system, offering short courses for NGOs, private sector and international organizations are suggested as activities to achieve the above goals. The role play of ICRAF Sri Lanka in networking institutes and scientists are discussed.
Keywords: Homegardens; Food Security; Nothern and Eastern Province